2020
DOI: 10.1037/rep0000361
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulatory efficacy for exercise in cardiac rehabilitation: Review and recommendations for measurement.

Abstract: Purpose: Self-regulatory efficacy (SRE) is a psychological resource necessary for cardiac rehabilitation (CR) exercise adoption and maintenance. A 2008 review of self-efficacy for CR exercise identified the need for more high-quality research on SRE. The present review had 4 purposes: (a) to review the characteristics of empirical SRE and CR exercise research since 2008; (b) to examine the quality of SRE measurement; (c) to determine whether varying quality of SRE measurement moderated the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In terms of mediating variables, internal constructs such as locus of control and self-efficacy, but not externally-focused perception of social support, improved during the intervention, suggesting that these may be factors that helped participants to become more physically active. Of these variables, self-efficacy may be particularly important, given the literature suggesting that self-efficacy for exercise is a major contributor to engaging in (and increasing) physical activity, and future studies should examine the mediating effects of this variable (Bauman et al, 2012 ; Locke, McMahon, & Brawley, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of mediating variables, internal constructs such as locus of control and self-efficacy, but not externally-focused perception of social support, improved during the intervention, suggesting that these may be factors that helped participants to become more physically active. Of these variables, self-efficacy may be particularly important, given the literature suggesting that self-efficacy for exercise is a major contributor to engaging in (and increasing) physical activity, and future studies should examine the mediating effects of this variable (Bauman et al, 2012 ; Locke, McMahon, & Brawley, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] For instance, positive outcome expectations (eg, manage better irregular heart rhythm if physically active) and high task selfefficacy (ie, confidence to engage in MVPA) have been shown to be significantly associated with increased PA in physically inactive adults and individuals with CVD, respectively. 24,25 In patients living with AF, our CHAMPLAIN-AF study 15 found that most patients had positive outcome expectations and moderate confidence to engage in PA. Moreover, we found significant positive relationships in outcome expectations, task self-efficacy, and PA levels and sitting time.…”
Section: What Is Novel?mentioning
confidence: 94%
“…This is consistent with results from a previous study that reported the highest level of self-efficacy at the beginning of a CR programme 142 . Self-efficacy is one of the most widely known key factors for improving adherence to exercise in all populations 116 , and is related to exercise behaviour during and following CR 143 . Cederbom et al 73 showed that selfefficacy for exercise improved for an individually tailored BMIP group of older women from the values obtained from receiving regular physical activity advice, but, consistent with Study B, self-efficacy between the groups was not significantly different 73 .…”
Section: Physical Fitness Psychological Outcomes and Hrqolmentioning
confidence: 99%